ENHANCING THE PROFESSIONAL PREPARATION OF FUTURE TEACHERS THROUGH COACHING TECHNOLOGIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This scientific article explores the utilization of coaching technologies in improving the professional preparation of future teachers. With the evolving landscape of education, there is a growing need to equip aspiring educators with the skills and competencies essential for effective teaching practices. Coaching technologies offer innovative tools and methodologies to enhance teacher training, foster reflective practices, and facilitate personalized professional development. This article discusses the significance of professional preparation for future teachers, examines the benefits of coaching technologies, and proposes strategies to leverage these tools effectively in teacher education programs.